Covalent Warheads Targeting Cysteine Residue: The Promising Approach in Drug Development - Fangjiao Huang; Xiaoli Han; Xiaohui Xiao; Jinming Zhou (Molecules, 2022)
Cysteine is one of the least abundant amino acids in proteins of many organisms, which plays a crucial role in catalysis, signal transduction, and redox regulation of gene expression. The thiol group of cysteine possesses the ability to perform nucleophilic and redox-active functions that are not feasible for other natural amino acids. Cysteine is the most common covalent amino acid residue and has been shown to react with a variety of warheads, especially Michael receptors. These unique properties have led to widespread interest in this nucleophile, leading to the development of a variety of cysteine-targeting warheads with different chemical compositions. Herein, we summarized the various covalent warheads targeting cysteine residue and their application in drug development.